"Sober encounters": the neoliberal logics of human rights documentary and Indian feminist documentary filmmakers. Issue 2 (3rd March 2016) - Bandi, Swati
Abstract: "Sober encounters" examines the market-defined encounters between Indian feminist documentary filmmakers and global humanitarian and media commissioning and funding agencies. Drawing from interviews conducted with Indian filmmakers, the essay looks closely at the seemingly sober aesthetic and ethical imperatives of these agencies and their impact on the production and distribution of rights-based feminist documentary film in India. Further, I present the figure of the "transient subject" and posit that it is one apprehended by market-friendly representational regimes to legitimate a neoliberal rights discourse. I argue for a deeper examination of these representational regimes and their attempts to de-radicalize the visual cultures of women's rights.